Romun kolinaa ja piirien värinää: Neljä suomalaista 2000-luvun kokeellisten hälysoitinten rakentajaa - Atte Häkkinen (Suomen Musiikkitieteellinen Seura, 2022)
My article deals with experimental instrument building in Finland in the 2010s. My goal is to conduct a case study of Finnish experimental instrument building. The methodology of the research project is based on cultural music research and ethnographic fieldwork. Cultural music research always understands music and musical practices as culturally constructed in their meanings. This premise guides my approach to interpreting the historical, social, and cultural significance of experimental musical instruments.
In my article, I deal with four case examples. The first case is media artist Sara Milazzo whose art works include sculptures, plastic collages, and collage-like paintings. She is a member of the Experimental Electronics Society (KOELSE) and also performs gigs based on electronic sound. Milazzo uses discarded electronics as material in her art works. My second example is media artist Sirpa Jokinen. In her art works, Sirpa Jokinen deals with the problems of surrounding space and location. In her recent works she has focused on alternative ways of reproducing sound and thereby listening to space. The third case is media artist, electronics designer and art educator Olli Suorlahti. Suorlahti makes music for the group Rantaremmi. He also appears as the solo project Bugari Ormond. Suorlahti has been a founding member of KOELSE in Helsinki in 2002 and KOKOMYS (Friends of Home Appliance Music Association) in Turku in 2007. Currently he is a member of the Videokaffe Art Collective which has existed since 2011. The fourth case is media artist Jukka Hautamäki. Hautamäki uses sound, light, electronics and video in his art works.
Experimental music in the 2010s combines maker culture and DIY (Do it yourself). Maker culture refers to a form of culture in which operators take over technology and build equipment and systems themselves. DIY is a concept that has a more sub-cultural meaning and is often used to refer to underground music. One of the most important features of experimental musical instrument building is intermedia. All of my informants call themselves media artists. Media can be sound, visual stimulus or something else, but usually it is a combination of different elements. Through media it is possible to take a stand on environmental issues. Environmental thinking also emerges through the artists’ working methods.